CircEPDR1 regulates proliferation and differentiation of goat skeletal muscle satellite cells through miR-345-3p/Akirin1 axis - Song Shi; Diansong Duan; Jing Luo; Zihao Zhao; Tao Ma; Dinghui Dai; Siyuan Zhan; Jiaxue Cao; Jiazhong Guo; Tao Zhong; Linjie Wang; Hongping Zhang; et al. (Animal Bioscience)
Objective Circular RNAs (circRNAs) play pivotal roles in regulating the growth and development of mammalian skeletal muscle This study aims to provide new insights into the molecular regulatory network that underlies skeletal muscle development, presenting valuable targets to enhance and optimize livestock production performance. Methods In this study, we anchored a novel circRNA from previous circRNA sequencing data from goat skeletal muscle and named it circEPDR1, which was confirmed through en-zymatic digestion and Sanger sequencing. Functional investigation of circEPDR1 included overexpression experiments in goat muscle satellite cells (MuSCs), and its sub-cellular localization was determined using nuclear-cytoplasmic separation. Bioinformatics analysis was employed to reveal a circRNA-miRNA-RNA regulatory pathway involving circEPDR1. This process was further validated through Dual-luciferase reporter assay, real-time fluorescence quantitative polymerase chain reaction, Western blotting, EdU incorporation, CCK-8 cell viability tests, and immunofluorescence experiments. Results We newly identified circEPDR1, which is produced by reverse splicing the second and third exons of the EPDR1 gene. circEPDR1 was enriched in skeletal muscle and dynamically expressed during the growth of goat MuSCs. In addition, circEPDR1 significantly inhibited the proliferation while promoting myogenic differentiation of goat MuSCs. The dominant cytoplasm distribution and enrichment by the AGO2 protein imply that circEPDR1 potentially works as a competitive endogenous RNA. Mechanically, miR-345-3p directly targeted circEPDR1, and its function in myogenesis was completely reversed to that of circEPDR1. Meanwhile, miR-345-3p negatively regulated Akirin1 mRNA through their base-pairing. Similar to circEPDR1, Akirin1 suppressed proliferation while also promoting differentiation. Conclusion This study demonstrates that circEPDR1 controls a vital role in regulating the proliferation and differentiation of goat MuSCs through the circEPDR1/miR-345-3p/Akirin1 axis.